2006
DOI: 10.1111/j.1525-1497.2006.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality conference, grand rounds, and the ACGME’s core competencies

Abstract: Morbidity and Mortality (M&M) Conferences are an Accreditation Council for Graduate Medical Education (ACGME) mandated educational series that occur regularly at all institutions that have residency training programs. The potential for learning from medical errors, complications, and unanticipated outcomes is immense--provided that the focus is on education, as opposed to culpability. The education innovation described in this manuscript is the manner in which we have used the ACGME Outcome Project's 6 core co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 15 publications
1
78
0
1
Order By: Relevance
“…Classic among these is the traditional Morbidity and Mortality (M and M) Conference. 75 Though long a symbol of medicine's old shame and blame culture, M and M conferences offer the opportunity for thoughtful review and analysis of real patient safety occurrences and for the active participation of students, residents and other health care professionals, such as nurses and pharmacists, in this process. Exploration of team functioning (or malfunctioning) is another potential by-product of such discussions.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Classic among these is the traditional Morbidity and Mortality (M and M) Conference. 75 Though long a symbol of medicine's old shame and blame culture, M and M conferences offer the opportunity for thoughtful review and analysis of real patient safety occurrences and for the active participation of students, residents and other health care professionals, such as nurses and pharmacists, in this process. Exploration of team functioning (or malfunctioning) is another potential by-product of such discussions.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…The closest category we found included studies that either asked the residents to rate the learning value of morbidity and mortality conferences or that correlated conference attendance with In-Training Examination scores. [15][16][17] In our introduction, we posed the following question: How do we effectively teach about circumstances so rare that a trainee may never see them clinically, yet when exposed to an uncommon situation for the first time, major patient morbidity or mortality may result? This pilot study begins to answer the question by providing a working model for teaching this critical information and by developing methods to measure the success of knowledge acquisition and retention.…”
Section: Discussionmentioning
confidence: 99%
“…One such initiative 2,3 involves the systematic use of data culled from the M&M conference to implement quality improvement in patient safety. Others 4,5 have suggested that the M&M conference can be used to teach the core competencies (patient care, medical knowledge, practice-based learning, interpersonal and communication skills, professionalism, and system-based practice). Most recently, education in end-of life care has been incorporated into the structure of the M&M conference in a neonatal intensive care unit.…”
Section: Introductionmentioning
confidence: 99%